Knotting the banner : ritual and relationship in Daoist practice - Mozina, David J. (New Daoist studies., 2021)
In the hills of China's central Hunan province, an anxious young apprentice officiates over a Daoist ritual known as the Banner Rite to Summon Sire Yin. Before a crowd of masters, relatives, and villagers--and the entire pantheon of gods and deceased masters ritually invited to witness the event--he seeks to summon Celestial Lord Yin Jiao, the ferocious deity who supplies the exorcistic power to protect and heal bodies and spaces from illness and misfortune. If the apprentice cannot bring forth the deity, the rite is considered a failure and the ordination suspended: His entire professional career hangs in the balance before it even begins.This richly textured study asks how the Banner Rite works or fails to work in its own terms. How do the cosmological, theological, and anthropological assumptions ensconced in the ritual itself account for its own efficacy or inefficacy? Weaving together ethnography, textual analysis, photography, and film, David J. Mozina invites readers into the religious world of ritual masters in today's south China. He shows that the efficacy of rituals like the Banner Rite is driven by the ability of a ritual master to form an intimate relationship with exorcistic deities like Yin Jiao, which is far from guaranteed. Mozina reveals the ways in which such ritual claims are rooted in the great liturgical movements of the Song and Yuan dynasties (960-1368) and how they are performed these days amid the social and economic pressures of rural life in the post-Mao era.Written for students and scholars of Daoism and Chinese religion, Knotting the Banner will also appeal to anthropologists and comparative religionists, especially those working on ritual.